Ethnomathematics: Mathematical Concepts in Sigale-Gale Statues - Fadhilah, Adinda Ayu; Lubis, Mara Samin (Indonesian Journal of Science and Mathematics Education, 2023)
This study aims to investigate the mathematical concept of the Sigale-gale statue so that it can be utilized as an instructional resource in mathematics. The study employs qualitative approaches using an ethnographic approach. The researcher served as the data collector for the study, and the informants were the Batak people. Primary data-gathering methods include observation, interviews, documentation, and comprehensive literature reviews. The data analysis technique is descriptive analysis in the form of data reduction, data presentation, and conclusion drawing. The results revealed that the Sigale-gale Sculpture contains mathematical concepts such as plane geometry, spatial geometry, reflection transformation, dilation transformation, and angles. Ethnomathematics can be an innovation as well as a breath of fresh air in the classroom learning process so that the methods used are not monotonous, ethnomathematics-based learning models, student worksheets, and visual videos that illustrate mathematical concepts on the Sigale-gale Statue are used, thereby increasing student motivation and interest, and student learning outcomes are also increasing.